Petrus Biverus’s Sacrum Oratorium and Sacrum Sanctuarium (Antwerp, 1634): Balthasar Moretus’s Preference for Pearls over Glass - Imhof, Dirk (Library, 2023)
Abstract In the first half of the seventeenth century the Plantin-Moretus Press of Antwerp was widely known for the high quality of its editions. One such case are two editions composed by the Spanish Jesuit Petrus Biverus published in 1634, namely: the Sacrum Oratorium piarum imaginum immaculatae Mariae and the Sacrum sanctuarium crucis. Both publications are well known for their numerous illustrations and as noteworthy emblem books. Nevertheless, correspondence between Moretus and Biverus reveals that Biverus was displeased with the high selling price of his books, while Moretus’s responses to Biverus’s remarks provide a rare view of how he envisioned his work as a publisher. In this article, I discuss this tension between the production costs and the author’s expectations. Like many other Jesuit authors, Biverus forgot that a publisher’s aim was to make a profit; Moretus forgot that authors want to have their books read and known by as many readers as possible.